Attitudes towards school violence based on aporophobia. A qualitative study - Pina, David; Marín-Talón, María Catalina; López-López, Reyes; Martínez-Andreu, Lucía; Puente-López, Esteban; Ruiz-Hernández, José Antonio (Frontiers in Education, 2022)
School violence is a worldwide problem. Among the variables that influence its frequency, perceived socioeconomic status seems to be associated with a higher risk of exposure to violence and attitudes toward violence. The aim of this study is to examine attitudes toward violence based on socioeconomic discrimination (aporophobia) and its relationship with violent behaviors in the school context. For this purpose, 96 Spanish students of Primary Education (PE) and Compulsory Secondary Education (CSE) participated in this qualitative study through focus groups and thematic analysis. The results identified three types of attitudes toward violence directed toward those who are perceived as members of a lower status. The attitudes observed are related to self-esteem or feeling better, legitimization and socialization.